Developing a Valid and Reliable Perceived Global Future Scale - Bodur, Gonul; Seren, Arzu K. Harmanci; Harmanci Seren, Arzu K. (Wiley, 2022)
Purpose To develop a valid and reliable data collection tool to define individuals' perceptions of the global future. Design and Methods This methodological study was carried out on 870 participants in Istanbul, a city with the country's highest and most diverse population. Findings Content validity, construct validity, item analyses, and stability of the draft tool were tested. The seven-factor scale structure was confirmed. Cronbach's alpha coefficient of the scale was .93. Practice Implications The Perceived Global Future Scale, consisting of 36 items and seven dimensions, was used. It is a valid and reliable tool to define perceptions of individuals on the global future.
Bodur, Gonul/0000-0002-2811-534X; HARMANCI SEREN, ARZU KADER/0000-0002-4478-7234
Keywords: Health; Nursing; Perceived Future; Reliability-Validity